Prevalence and predictors of intestinal worm infections among Semai Aboriginal Tribe School Children in Tapah, Malaysia - Tunbosun, Olawumi Edward; Gyanchand Rampal, Lekhraj Rampal; Abdul Rahman, Hejar; Abdul Majid, Roslaini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Worm infection is one of the major global public health problems especially among rural communities. Objectives: to determine the prevalence of intestinal worm infection and factors associated among Semai Aboriginal children aged between 6 to 13 years in Tapah, Malaysia. Methods: A cross-sectional study design was used in this study. The estimated sample size was 508. Data was collected using a validated pretested questionnaire. Faecal samples were also examined. Data was analysed using SPSS version 22. Results: The response rate was 80.9%. The overall mean age of the 411 respondents was 10.1 years(95% CI = 9.89, 10.22). Majority (71.5%) were poor. Prevalence of intestinal worm infections was 60.8% and 57.2% had multiple infections. The multiple logistic regression analysis showed that those with poor hygiene practices were 2.18 times the odds of worm infection when compared with children with good hygiene practices (95% CI = 1.4, 3.4). Similarly, poor attitudes towards prevention of worm infection increased the odds of having worm infection by 1.62 times among Orang Asli children. Children living without toilets had 2.45 times higher odds as compared with those who had proper toilets. Absence of river near by these areas where there is no safe water supply also increases the risk of worm infection among children by 1.84 times among Orang Asli children. Conclusions: the prevalence of worm infection is still very high among rural Aboriginal community. Current control measures should be reassessed to enable introduction of effective measures to reduce the worm infection among Orang Asli children.